Determinants of Firm Value in Indonesian Pharmacies (International Journal of Scientific Research and Management (IJSRM), 2024)
This research aims to determine the factors affecting the firm value of 10 pharmaceutical companies listed on the Indonesia Stock Exchange for the period of 2018-2022. The methodology used in this research is a quantitative approach to analyze the relationship between the variables and their impact on firm value. The research results found that profitability and company growth had no impact on firm value, but liquidity and leverage did. These results indicate that changes in stock prices are not caused by profitability or company growth, but rather by the liquidity and leverage of the pharmaceutical companies listed on the Indonesia Stock Exchange for the period of 2018-2022. The findings of this research can be recommended to investors to help identify the factors that affect firm value and serve as a basis for making investment decisions in pharmaceutical companies.